Effects of Heart Rate Variability Biofeedback in Subjects with Stress-Related Chronic Neck Pain: A Pilot Study - Hallman, David M.; Olsson, Erik M. G.; von Schéele, Bo; Melin, Lennart; Lyskov, Eugene (Applied psychophysiology and biofeedback, 2011)
Recent studies focusing on autonomic nervous system (ANS) dysfunctions, together with theoretical pathophysiological models of musculoskeletal disorders, indicate the involvement of ANS regulation in development and maintenance of chronic muscle pain. Research has demonstrated the effectiveness of heart rate variability (HRV) biofeedback (BF) in increasing HRV and reducing the symptoms of different disorders characterized by ANS aberration. The study investigated the effects of resonance frequency HRV BF on autonomic regulation and perceived health, pain, stress and disability in 24 subjects with stress-related chronic neck-shoulder pain. Twelve subjects participated in 10 weekly sessions of resonant HRV BF and were compared to a control group. Subjective reports and HRV measures during relaxation and in response to a standardized stress protocol were assessed for both groups pre- and post-intervention. Group × time interactions revealed a significantly stronger increase over time in perceived health (SF-36) for the treatment group, including vitality, bodily pain and social functioning. Interactions were also seen for HRV during relaxation and reactivity to stress. The present pilot study indicates improvement in perceived health over a 10 week intervention with HRV-biofeedback in subjects with chronic neck-pain. Increased resting HRV as well as enhanced reactivity to hand grip and cold pressor tests might reflect beneficial effects on ANS regulation, and suggest that this intervention protocol is suitable for a larger controlled trial.